G4-binding drugs, chlorpromazine and prochlorperazine, repurposed against COVID-19 infection in hamsters - Roy, Shuvra Shekhar; Sharma, Shalu; Rizvi, Zaigham Abbas; Sinha, Dipanjali; Gupta, Divya; Rophina, Mercy; Sehgal, Paras; Sadhu, Srikanth; Tripathy, Manas Ranjan; Samal, Sweety; Maiti, Souvik; Scaria, Vinod; et al. (Frontiers in Molecular Biosciences, 2023)
The COVID-19 pandemic caused by SARS-CoV-2 has caused millions of infections and deaths worldwide. Limited treatment options and the threat from emerging variants underline the need for novel and widely accessible therapeutics. G-quadruplexes (G4s) are nucleic acid secondary structures known to affect many cellular processes including viral replication and transcription. We identified heretofore not reported G4s with remarkably low mutation frequency across >5 million SARS-CoV-2 genomes. The G4 structure was targeted using FDA-approved drugs that can bind G4s - Chlorpromazine (CPZ) and Prochlorperazine (PCZ). We found significant inhibition in lung pathology and lung viral load of SARS-CoV-2 challenged hamsters when treated with CPZ or PCZ that was comparable to the widely used antiviral drug Remdesivir. In support, in vitro G4 binding, inhibition of reverse transcription from RNA isolated from COVID-infected humans, and attenuated viral replication and infectivity in Vero cell cultures were clear in case of both CPZ and PCZ. Apart from the wide accessibility of CPZ/PCZ, targeting relatively invariant nucleic acid structures poses an attractive strategy against viruses like SARS-CoV-2, which spread fast and accumulate mutations quickly.